ARTIFICIAL INTELLIGENCE AS AN INSTRUMENT FOR LOCAL GOVERNMENT DECISION-MAKING: OPPORTUNITIES, RISKS, AND GOVERNANCE CHALLENGES - Mujahidin (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
This study aims to analyze artificial intelligence as an instrument for supporting local government decision-making, with particular attention to its opportunities, risks, and governance challenges. The study focuses on AI use in public services, licensing administration, and community-needs analysis, while emphasizing that AI must not replace the role of authorized public officials in governmental decision-making. This research uses a qualitative method with an exploratory-descriptive approach and conceptual governance framework development. Data were collected from secondary and documentary sources, including recent peer-reviewed journal articles, policy documents, institutional reports, regulatory materials, and scholarly works related to AI, automated decision-making, digital governance, local government administration, explainable AI, and public-sector ethics. The data were analyzed using thematic analysis by classifying findings into AI opportunities, algorithmic risks, human oversight, explainability, administrative accountability, institutional readiness, and ethical safeguards. The findings show that AI can support bureaucratic decisions by improving document screening, service-priority classification, licensing risk assessment, complaint analysis, eligibility recommendation, and identification of community needs. The study also finds that AI may create risks of algorithmic bias, opacity, privacy violation, automation bias, and administrative exclusion. The main contribution of this study is the formulation of a human-supervised AI decision-support framework consisting of data governance, AI-based administrative analysis, human verification, accountable decision-making, and citizen redress mechanisms.